A classificação de Bianchi e a construção de Taub das métricas cosmológicas anisotrópicas - Scardini, Lucas Oliveira (2024)
The study of the cosmos is of utmost importance for understanding the origin of the Universe. One of the foundations in these studies is the metric used, which is commonly homogeneous and isotropic. However, there are works that utilize anisotropic or inhomogeneous metrics. Anisotropic metrics have been divided into different types by the work of Abraham Taub, who based his classification on Luigi Bianchi’s classification of anisotropic manifolds. This dissertation has two objectives: the first is to construct anisotropic metrics starting with a simple review of general relativity. The second is to demonstrate the importance of studying models that do not adhere to the cosmological principle